STRUCTURAL STUDY OF PEPACCUR ORAL LITERATURE LAMPUNG PEPADUN COMMUNITIES IN THE PROCESSION OF TAKING CUSTOM DEGREE - Dewi Ratnaningsih (Universitas PGRI Palembang, 2020)
Pepaccur is a type of Lampung poetry which contains advice or message in the customary degree ceremony. In this research, data was collected from several regions belonging to the Lampung Abung community, such as Kotabumi Ilir, Blambangan Pagar, Surakarta, Bumi Agung, and Mulang Maya. The problem that will be examined in this study is about the structure contained in Pepaccur. The purpose and benefits of this study are (1) to determine the Pepaccur structure in the Pepadun community in the procession of taking traditional titles; (2) to revitalize Pepaccur Lampung Pepadun people. Descriptive method through qualitative approach is the method used in this study. Data collection techniques used in this study are (1) observation, (2) recording, and (3) interview. Data analysis techniques are carried out by identifying the Pepaccur structure. Based on ethnographic studies that are used as a foothold in this study the Pepaccur structure consists of a framework, diction, sound, tone, and class. (1) Pepaccur framework. Of the 6 Pepaccur text samples, there is only one Pepaccur text that does not have an opening stanza, ie in Pepaccur II text. In addition, the Pepaccur II text is also a text in the form of stories to bind Lampung women. (2) Pepaccur's diction. Based on the results of the analysis, the diction used by people who are Pepaccur is a diction related to marriage. (3) Pepaccur sounds. the sound found in Pepaccur text analysis is a sound pattern abc / abc, ab / ab, aa / aa, a / a. (4) Pepaccur tones. The tone in Pepaccur's text is advising. (5) figurative language. The figurative language found in the Pepaccur text includes; allegory, metaphor, and simile.Keyword: Pepaccur, Lampung Poetry, Language Structure